Complete genome sequences of 13 human respiratory syncytial virus subgroup A strains of genotypes NA1 and ON1 isolated in the Philippines - Rungnapa Malasao (2018)
© 2018 Malasao et al. Complete genome sequences of 13 human respiratory syncytial virus strains were determined from samples obtained from children hospitalized in the Philippines between 2012 and 2013 because of acute respiratory infection. We identified amino acid polymorphisms between the NA1 and ON1 genotypes in the P, G, F, and L proteins.